How well do parents know their adolescent children? Parent inferences of student self-concepts reflect dimensional comparison processes. (February 2017) - Van Zanden, Brooke; Marsh, Herbert W.; Seaton, Marjorie; Parker, Philip D.; Guo, Jiesi; Duineveld, Jasper J.
Abstract: The internal/external frame of reference (I/E) model posits paradoxical relations between achievement and self-concept in mathematics and verbal domains. There is strong support for the I/E model based on student self-ratings, however, reviews of self-concept research claim that the I/E model does not apply to ratings by parents and significant others. We aimed to test these claims using parent inferred self-concepts. In contrast to widely cited claims, we found support for I/E model for both students (N = 486; aged 11–17; 57.2% female) and their parents (80.5% female). Math and verbal achievement had positive effects on self-concepts in the matching domain (e.g., math achievement predicting math self-concept) but negative effects for self-concepts in the non-matching domain (e.g., math achievement predicting verbal self-concept). Integrating conflicting claims, we found support for dimensional comparison processes for inferred self-concept ratings by parents, but not for parent perceptions of student abilities similar to the measures used that were the basis of previous claims. Highlights: Dimension comparison processes are critical to self-concept formation of students. Achievement in one area can have negative impacts on self-concept in the opposite domain. This paper addresses potential over-interpretation of past findings in self-concept reviews. The IE model applies to parent inferred self-concepts, but not perceptions of child ability.